2019
DOI: 10.33512/jpk.v9i1.7077
|View full text |Cite
|
Sign up to set email alerts
|

Gonad Maturity Rate of Gray Eeltailed Catfish with Different hCG Induction

Abstract: Gray eeltailed catfish is one of the local commodities in the Riau Islands. Domestication and aquaculture has not been done. Reproduction is one of problems in the Aquaculture effort. Gonadal maturity is stage preparation of the prospective parent for spawning process. One of efforts to gonad maturation is hormonal induction. This study purpose to determine effect of various brands hCG hormones on gonad maturity and determine the best hCG hormone brands that can accelerate the maturity of gonad fish crossing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Furthermore, Egg diameter increased in each treatment from the beginning to the end of the study. The results of this study indicated that the high value of egg diameter were treatment C. Yulianto et al [25] concluded that Oodev hormone contains PMSG hormone, where the FSH content is greater and the LH is less. FSH functions for egg maturation and LH functions for egg production.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, Egg diameter increased in each treatment from the beginning to the end of the study. The results of this study indicated that the high value of egg diameter were treatment C. Yulianto et al [25] concluded that Oodev hormone contains PMSG hormone, where the FSH content is greater and the LH is less. FSH functions for egg maturation and LH functions for egg production.…”
Section: Discussionmentioning
confidence: 54%
“…The vitellogenesis process in fish is responsible for the rise in GSI values [14]. The vitellogenesis process will continue until the fish spawns, at which point the gonads will develop in weight and size in tandem with the growth of the gonads, reaching their maximum size when the fish spawns [15]. The gonado index is computed by comparing body length, which is linked to fish growth.…”
Section: Discussionmentioning
confidence: 99%
“…Kandungan pada Oodev memiliki hasil yang baik terhadap kematangan telur. Sejalan dengan pendapat Yulianto et al (2019) menyatakan bahwa FSH berfungsi pada proses ovulasi dan pematangan oosit sehingga ukuran diameter telur dapat bertambah dan pematangan oosit terbentuk sempurna karena pengaruh fungsi hormon gonadotropin yang diberikan. Rangsangan hormonal yang sesuai dapat meningkatkan diameter oosit yang dihasilkan oleh penyerapan lumen ovari.…”
Section: Hasil Dan Pembahasanunclassified